A proposed strategic plan for Canibad Beach Resort - Caliao, Joy d. (School of Management, University of the Philippines Mindanao, 2007)
Canibad Beach Resort is a seaside vacation spot of pristine beauty that promises great outdoor adventure for nature lovers. This paper was intended as a blueprint of this resort?s strategic direction for the next five years, from 2008 to 2012, based on an analysis of its internal and external environments as well as its business objectives. The data used in this study were gathered from primary and secondary sources and were processed using the Strategic Decision Making Process Model of T.L. Wheelen and J.D. Hunger (Wheelen and Hunger, 1994). This involved the systematic gathering of appropriate information for situation analysis, the generation of feasible alternative strategies, and the rational selection of the most appropriate strategy. The TOWS Matrix was used to formulate the strategic alternatives of Canibad Beach Resort. These options were trimmed down into a specific strategic choice using the Quantitative Strategic Planning Matrix (QSPM). This researcher recommends ?Concentrated Growth?, which had the highest QSPM score of 5.70, as the corporate strategy of the subject company. This means that Canibad Beach resort has to focus on a growth strategy that directs its resources towards stimulating a profitable growth of the resort?s services in a single market within the eco-tourism industry.